Pembangunan Knowledge Management System Mahasiswa Politeknik Statistika STIS - Annisa Adytia Putri; Ibnu Santoso (Seminar Nasional Official Statistics, 2022)
Knowledge Management System (KMS) is a system for processing knowledge collection, from identification to dissemination. Universities can use KMS in managing knowledge to facilitate access of information and improve administrative processes. This research focuses on the development a web KMS for Polstat STIS students using the KMSLC development method. Knowledge is devoted to non-academic knowledge in Polstat STIS. The total knowledge that has been collected and verified is 48. KMS evaluation is done with Black box, PPSUQ, Webqual 4.0, and testing the search feature. PSSUQ KMS score for overall satisfaction obtained is 1.8. The more closer to one, the better test results. The percentage of Webqual (98.7%) of respondents agreed with the quality of knowledge. As for the search feature, 99.1% of respondents also agree with the two statements on the search feature test. From the processes carried out, the KMS that was built was able to achieve the purposes of this research.